108 - HUMANIZED PRENATAL: A RIGHT FOR EVERY PREGNANT WOMAN (Fiep Bulletin - online, 2011)
Prenatal care comprises an entire assistance behavior to the pregnant woman before childbirth; with the purpose of diminishing the neonatal and motherly mortality. To have a humanized and effective assistance, a precocious identification of every pregnant woman is required to start the accompaniment in the first quarter. The health group has to carry out a periodic and continuous attention to assist the woman in the health unity as well as in her house, giving clarifications and relevant information about all the pregnancy stages and the fetus development. Since the Health Ministry created through GM law nº 569 on August 18, 2000, the Humanization in the Prenatal and Birth Program (HPBP), the assistance of the health services has expanded in all country. The present work evaluated the prenatal quality carried out by a health group in the Basic Unity of Family Health Program, in the district of Nova Brasilia from Campina Grande-PB, Brazil. The study was a descriptive and quantitative search that utilized formularies with objective and subjective questions. The sample was comprised of 31 pregnant women from 14-20 years (39%), 21-27 years (42%), 28-34 years (13%) and 35 years and more (6%). The pregnant women that had others sons corresponded to 68% and all participants breast-fed in the other pregnancy. The consultations were made by nurses and doctors. About the pregnant women questioned, 16% made two or three consultations; 32%, four or five, and 52%, six or more as the Health Ministry determined. The number of exams was solicited according to what is determined by HPBP; ABO-Rh (1), VDRL (2), Urine Summary (2), Blood Glucose (2), blood count (2) and HIV test (1). The HIV was not performed to every pregnant woman, since some did not want it performed. Pregnant women were advised to receive an anti- tetanus vaccine (dt) and they participated in educational and health discussions. The behavior of the health group was evaluated as very good by 68% of women. Concerning actual prenatal care, the participants mentioned that they received a humanized assistance, good attendance, orientation, accompaniment and psychological care.
Keywords: Pregnancy; Prenatal; Humanization